Feasibility Analysis of Smart Wheelchairs Based on Voice Recognition for People with Disability - Fathanah Muntasir, Nurul; Muhammad Risafli Raif; Rahmat Hermawan; Muh. Anshar (Enthusiastic : International Journal of Applied Statistics and Data Science, 2023)
Technological developments have accelerated the advancement of assistive technology, hence increasing human life feasibility. One of which is smart wheelchairs with a voice recognition to facilitate people with disability. However, from various smart wheelchair developments, there have been no detailed test results related to the efficiency analysis, the feasibility of the voice recognition feature on the smart wheelchair, and the satisfaction of users in using it. In this study, observations were conducted using a simple regression method, and test user satisfaction using the USE questionnaire. Based on calculation results, the learnability score was 78.81%, indicating that the wheelchair was easy to understand. The efficiency score was 85%, meaning that users found it easy to carry out their daily activities. The memorability score was 85%, indicating that it was easy to remember. The error score was 77.38%, meaning that smart wheelchairs were easy to use. The satisfaction score was 88.57%, meaning that the users felt very comfortable. The conclusion is users are satisfied with smart wheelchairs using voice recognition, meaning that it provides feasible use for a variety of people with disability. The results can be used as a foundation in continuing the development of technological features in smart wheelchairs.